Comprehensive neurosurgical and visceral surgical therapy of retroperitoneal nerve tumors: a descriptive and retrospective analysis - Martin Petkov; Marko Kornmann; Ute Marlies Bäzner; Lena Minzenmay; Andrej Pala; Maria Teresa Pedro; Christian Rainer Wirtz; Gregor Antoniadis (World Journal of Surgical Oncology)
Abstract Nerve tumors in the retroperitoneal space are a rarity. Radical surgery according to soft tissue tumors can lead to persistent pain and neurological deficits. This study aims to evaluate clinical outcomes of patients treated by a visceral- / neurosurgical approach. 33 patients with a retroperitoneal nerve tumor underwent surgery between 01/2002 and 12/2022 at our department. A visceral surgeon provided access to the retroperitoneal space, followed by micro-neurosurgical tumor preparation under neuromonitoring. Clinical examination and MRI were performed 12 weeks after surgery and further 3 months (WHO grade > 1) or 12 months (WHO grade 1). Further examinations were based on MRI findings and residual symptoms with median follow-up time of 24 months. One patient was treated for two distinct masses resulting in a total of 34 histological findings. Schwannomas (n = 15; 44.1%) and neurofibromas (n = 10; 29.4%) were the most common tumors. Long-term improvements were noted in radicular pain (15/18 patients; 83.3%), motor deficits (7/16 patients; 43.8%), abdominal discomfort and pain (5/7 patients; 71.4%). Recurrences were observed in 3/33 (9,1%) patients. This study represents the largest series of retroperitoneal BPNSTs treated with microsurgical techniques. Prospective multicenter studies are warranted to establish standardized treatment guidelines.